OECD BEPS: Reconciling global trade, taxation principles and the digital economy - Hosuk Lee-Makiyama; Bert Verschelde (European Centre for International Political Economy (ECIPE), 2014)
Following media reports on the low tax rates paid by some of the world's largest multinationals, international tax reform has moved to the top of policy-makers' agendas across the world. At the request of the G20, the OECD has designed an action plan to address what it calls base erosion and profit shifting (BEPS) - namely that the corporate tax base is eroding due to the internet. However OECD itself admits there is no evidence of base erosion in reality. Nonetheless, some OECD and EU Member States are targeting the digital economy as the main culprit for alleged erosion of corporate tax income. A new ECIPE report by Hosuk Lee-Makiyama and Bert Verschelde raises doubts on facts and assumptions surrounding the OECD/EU work. The ECIPE report argues that the online companies in fact pay effective tax rates similar to other multinational business, and the only way to address the problem is introducing uniform VAT and corporate tax rates in the EU. The options currently considered in the OECD BEPS process is to require online businesses to have a local presence in every country they operate in, and thereby forcing them to pay taxes in these countries. This would not only contradict the OECD's own technology neutrality principle in taxation, but also reverse the free movement of services on the EU's single market, and in essence create a separate tax regime for the digital economy, despite intentions to the contrary. Furthermore, requiring online services to always establish a local presence would imply reneging on commitments on cross-border services trade made in multi- and bilateral free trade agreements. Furthermore, given the impact of ICT on productivity, international trade and ultimately economic growth, the cure could end up being worse than the disease.
Keywords: 330